Measurement of Halal Industry (Literature Review) - Muslikhati (Proceedings of Femfest International Conference on Economics, Management, and Business, 2023)
The halal industry is part of the world's supply chain. The use of halal raw materials in the halal industry is very important because every production industry requires input from other companies at home and abroad. The availability of halal raw materials is a necessity. Research on the halal industry is increasingly being carried out. Given the awareness of various parties (especially Muslims) who make halal indicators a key in their production activities. Research on halal supply chain collections uses the keywords halal industry and measurement between 2010 and 2021. The results of the review use 39 journals in the collection according to the topics of discussion around halal supply chain, halal industry and measurement. The findings show that the existence of the halal industry is very important. This is because the theme of the halal industry is needed to answer the challenges of community needs regarding the availability of halal products as a form of obligation in Islam. But unfortunately, research on measuring the halalness of products from the halal industry has not been carried out much. This happens because the measurement indicators are still very minimal and the availability of quantitative data in the halal industry is not widely available.